Effects of flower extract from Nelumbo nucifera on high-K+ & Ca2+-induced colonic contraction in diabetic rats - Sakuljaitrong, Supasorn; Buddhakala, Nopparat (Progress in Applied Science and Technology, 2016)
Gastrointestinal (GI) disorder has been commonly found in diabetic patients. Diabetes can also affect GI motility through changes in intestinal smooth muscle or alterations in extrinsic neuronal control. The exact mechanism of the intestinal is not fully understood. The aim of this study was therefore to investigate the effect of N. nucifera flower extract (NNFE) on high K+ and Ca2+-ion induced colonic contraction in diabetic rats. Male albino Wistar rats were induced with 65 mg/kg b.w. streptozotocin. All groups of rats were daily once oral administered of NNFE (250 mg/kg b.w.) for 8 weeks. The rats were sacrificed by asphyxiation with CO2. Longitudinal colonic smooth muscle strips of the rats were prepared for SNP-reduced contraction investigation. The results showed that NNFE significantly (p<0.05) reduced the contractile responses of colonic smooth muscle strips of the rats in the presence of K+ and Ca2+-ion. Also, NNFE significantly (p<0.05) reduced the responses of the strips in the presence of SNP. The changes in intracellular Ca2+ concentrations lead to fusion of insulin-containing vesicles to the plasma membrane and subsequent rapid exocytosis of insulin from β cells. The data indicated that in vivo study of the NNFE on hypoglycemic activity, producing 44% reduction in blood glucose levels and inhibited colonic contractile activity in diabetic rats.